2012
DOI: 10.3389/fphys.2012.00355
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk and Signaling Switches in Mitogen-Activated Protein Kinase Cascades

Abstract: Mitogen-activated protein kinase (MAPK) cascades control cell fate decisions, such as proliferation, differentiation, and apoptosis by integrating and processing intra- and extracellular cues. However, similar MAPK kinetic profiles can be associated with opposing cellular decisions depending on cell type, signal strength, and dynamics. This implies that signaling by each individual MAPK cascade has to be considered in the context of the entire MAPK network. Here, we develop a dynamic model of feedback and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
140
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 114 publications
(193 reference statements)
8
140
0
Order By: Relevance
“…Computational modelling has already provided an understanding of the dynamics of signaling pathways (16,(52)(53)(54). Here, we showed that modelling approaches can not only be used to decipher and understand the behavior of complex networks on the cellular level but that they also can be used to relate biochemical pathway behavior to clinical outcomes on the level of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modelling has already provided an understanding of the dynamics of signaling pathways (16,(52)(53)(54). Here, we showed that modelling approaches can not only be used to decipher and understand the behavior of complex networks on the cellular level but that they also can be used to relate biochemical pathway behavior to clinical outcomes on the level of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Complex dynamic behaviors emerge in these signaling systems, including all-or-none responses and hysteresis driving specific cell fate decisions, for instance, the synchronization of oscillators in the circadian rhythm and the encoding of information in the frequency of p53 pulses during the DNA damage response. 8,[49][50][51] Although the signal processing functions of many cellular systems, for instance kinase/phosphatase cascades, are well recognized [52][53][54] , a detailed understanding of small GTPase networks is largely missing. It is known that GTPase cascades can exhibit complex spatiotemporal dynamics, but how the cell controls the different dynamic behaviors and how GDIs are involved in this regulation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Specific heterotrimers dephosphorylate and stabilize tumor suppressors, such as p53 (5,6) and p107 (7); thus, PP2A activity is important in cell-cycle regulation and tumor suppression. PP2A has been shown to dephosphorylate positive regulators of cell signaling pathways such as ERK and Akt (8)(9)(10)(11), inhibiting them and promoting senescence or apoptosis. Inhibition of PP2A promotes enhanced cell proliferation, impairment of cell differentiation, malignant cell transformation (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%